2016
DOI: 10.1080/02640414.2016.1158852
|View full text |Cite
|
Sign up to set email alerts
|

What benefits does team sport hold for the workplace? A systematic review

Abstract: Physical inactivity is proven to be a risk factor for non-communicable diseases and all-cost mortality. Public health policy recommends community settings worldwide such as the workplace to promote physical activity. Despite the growing prevalence of workplace team sports, studies have not synthesised their benefits within the workplace. A systematic review was carried out to identify articles related to workplace team sports, including intervention, observational and qualitative studies. Eighteen studies met … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 36 publications
1
37
0
5
Order By: Relevance
“…Additionally, students learn to strengthen their confidence and self-esteem, and the development of social cognition is reinforced [2]. With respect to the social responsibility of physical education, Brinkley et al [3] underscored that team sport holds benefits not only for individual health but also for group cohesion and performance and organizational benefits, such as the increased work performance. Cronin et al [4] revealed that physical education can help students develop skills, such as teamwork, goal-setting, time management, emotional skills, interpersonal interaction, social skills, leadership, problem-solving, and decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, students learn to strengthen their confidence and self-esteem, and the development of social cognition is reinforced [2]. With respect to the social responsibility of physical education, Brinkley et al [3] underscored that team sport holds benefits not only for individual health but also for group cohesion and performance and organizational benefits, such as the increased work performance. Cronin et al [4] revealed that physical education can help students develop skills, such as teamwork, goal-setting, time management, emotional skills, interpersonal interaction, social skills, leadership, problem-solving, and decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…Exercise/gym classes, walking, active-transport, educational training, active work stations and activity challenges have been utilised in the workplace with varying degrees of effectiveness [ 3 ]. However, research to date is yet to comprehensively examine the efficacy of sport and team sport on health outcomes [ 4 ]. Indeed, a further critique of workplace PA literature has been the failure to assess the efficacy of participation against social group and organisational health outcomes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Participation in workplace team sport has the capacity to improve individual, social group and organisational health outcomes [ 4 ]. Several randomised control trial (RCT) and quasi-experimental studies demonstrate that participation in competitive or non-competitive team sports can significantly improve cardiorespiratory fitness, musculoskeletal function [ 6 – 9 ] and psychological wellbeing [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are extensive knowledge and research on the benefits of engagement in PA. For example, regarding team sports, Brinkley et al (2017) argued that it holds advantages for the individual (e.g., health, reduced stress and tension, well-being), for group (e.g., improved teamwork relations, team trust, and communication) and for organisational health (e.g., sickness absence; increase in work performance). Likewise, the engagement in PA by children is linked with social benefits (e.g., making new friends, and teamwork/social competencies) and personal benefits (e.g., emotional control, confidence, and academic performance) (Holt et al 2011).…”
Section: Physical Activity Levelmentioning
confidence: 99%
“…PA is linked to different benefits, such as stress reduction, increase in work performance (e.g., Brinkley et al 2017) and teamwork/social competencies (e.g., Holt et al 2011). In the context of entrepreneurship, Marques et al (2011a) argued that engaging in yoga enhances psychological and cognitive attributes commonly linked to entrepreneurial profile.…”
Section: Introductionmentioning
confidence: 99%